Driver behaviour of ethanol-impaired non-vehicular trauma victims. Issue 1 (March 1986) - Maull, K I; Clapp, A R; Ellis, L M
Abstract : During a recent 12-month period, a group of patients injured from causes other than road accidents were studied. Twenty-four patients with no evidence of alcohol impairment served as controls for another group of 24 patients with a blood alcohol concentration of greater than 100 mg%. Examination of public records revealed that the alcohol-impaired group had committed more serious traffic violations, including reckless driving, crashes causing bodily injury, and property damage. Eleven of the 24 alcohol-impaired subjects had a total of 18 previous citations for driving under the influence of alcohol while there were none in the control group (P less than 0.001). Alcohol-related non-vehicular trauma is highly predictive of alcohol-impaired driving behaviour.